"Once upon a time there was a little girl…": Colonialism, "illegitimacy", and speciesism in Scott Rankin's Beasty Girl: The Secret Life of Errol Flynn. (September 2019) - Smith, Karina
This article argues that Scott Rankin's play, Beasty Girl: The Secret Life of Errol Flynn, uses the life story of Errol Flynn as a metaphor for colonialism in order to contest colonial legal descriptors, such as terra, aqua, and filius nullius . The play focuses on the fictitious "illegitimate" Jamaican daughter of Flynn who travels to Tasmania to follow in her father's footsteps. The more Carly, Flynn's daughter, discovers about her father's life, the more she rejects his colonial values and, by extension, whiteness.